Examining the game-specific practice behaviors of professional and semi-professional esports players: A 52-week longitudinal study. (December 2022) - Pluss, Matthew A.; Novak, Andrew R.; Bennett, Kyle J.M.; McBride, Ignatius; Panchuk, Derek; Coutts, Aaron J.; Fransen, Job
Abstract: This study followed a longitudinal design to objectively monitor practice behaviors of professional and semi-professional esports players over a year. Publicly available data were collected from 30 male Counter-Strike: Global Offensive players (age: 23.76 ± 2.88y). Players were classified into two groups: professional (n = 18) or semi-professional (n = 12). The total hours of practice (all game-specific practice) and the competitive hours of practice (time spent in competitive modes only) were collected weekly. Generalised Estimating Equations were used to compare the practice behaviors of the two groups. Professional and semi-professional esports players completed an average of 30.9 ± 8.2 h and 24.7 ± 3.6 h per week of total game-specific practice, respectively, and 19.6 ± 6.9 and 15.0 ± 2.7 h of competitive practice, respectively. A significant week ∗ group interaction was observed for total practice time (Wald χ2 = 9.48, p = 0.002) and total competition practice time (Wald χ2 = 7.54, p = 0.006). Specifically, professional esports players completed 6.6 (SE = 2.2) hr per week more of total practice hours than semi-professional players, of which 4.8 (SE = 1.8) hr were competitive practice. This sample of expert esports performers complete high volumes of practice which can be monitored via publicly accessible repositories. Highlights: Public data repositories can be used to objectively and longitudinally monitor practice behaviors of esports players. Practice behaviors of professional and semi-professional esports players can involve >30 h/week of practice. Professional players accumulate more hours of practice per week than semi-professional players. A high volume of expert esports practice is performed in competitive, game-specific activities.